The Effect of Different Ethanol Concentrations as The Extraction Solvent on Total Flavonoid Content of White Mulberry Leaves Extracts (Morus alba L.) - Harpolia Cartika,; Khairun Nida,; Ilma Atania Ahya, (International Journal of Scientific Research in Science and Technology, 2024)
White mulberry leaves (Morus alba L.) contain flavonoid which empirically have many health benefits, such as reducing fever, relieving headaches and throats, coughs, dysentery, digestive disorders, flu, and according to research it has antioxidant activity. Many factors effect the total flavonoid content, one of which is the concentration of the extraction solvent. The purpose of the research was to determine the effect of different ethanol concentrations as the extraction solvent on total flavonoid content of white mulberry (Morus alba L.) leaves extract. White mulberry leaves (Morus alba L.) were extracted using the maceration method, the extract was tested for phytochemical screening and thin layer chromatography using chloroform: ethyl acetate (6: 4) as the eluent. The resulting spots were observed visually and with λ 254 nm and λ 366 nm UV light. Determination of flavonoid content by UV-Vis spectrophotometry using the AlCl3 colorimetric method at a maximum wavelength of 415 nm. The research results showed that the yield of 50% and 96% ethanol extract of white mulberry leaves (Morus alba L.) was 17.42 % and 11.04 %. Phytochemical screening showed that both extracts positively contained flavonoids. The presence of flavonoids was confirmed using a thin layer chromatography test, resulting in an average Rf value for 50% and 96% ethanol extracts are 0.71 and 0.70, close to quercetin Rf standard is 0,73 as comparison. The total flavonoid content obtained from the 50% ethanol extract was 36.0902 mgQE/g and the 96% ethanol extract was 56.4699 mgQE/g. The conclusions are the concentration of the extraction solvent effect the yield and total flavonoid content.
Keywords: White mulberry leaves; Morus alba L.; Flavonoid; Ethanol; UV-Vis Spectrophotometry